2015
DOI: 10.1186/s13018-015-0195-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 17 cases of posterior vertebral column resection in treating thoracolumbar spinal tuberculous angular kyphosis

Abstract: ObjectiveThis study aims to explore the efficacy and safety of posterior vertebral column resection (PVCR) in treating thoracolumbar spinal tuberculous angular kyphosis (TSTAK).MethodsFrom January 2008 to January 2012, 17 TSTAK patients were treated surgically, including five males and 12 females, with an average age of 23.6 years, among five cases who had the kyphotic apical vertebrae located at the thoracic vertebrae, ten cases were located at the thoracolumbar segment, and two cases were located at the lumb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…In cases with severe kyphosis, osteotomies are essential to reconstruct the sagittal alignment. Various techniques have been described for correcting post-tubercular kyphosis, including pedicle subtraction osteotomy [ 8 ], closing-opening wedge osteotomy [ 9 , 10 ], and vertebral column resection [ 11 18 ]. Due to the complexity of severe post-tubercular kyphosis and accompanying late-onset neurological deficits, posterior vertebral column resection (PVCR) seems to be the most effective surgery that allows for sufficient correction of the deformity and decompression of the spinal cord [ 12 14 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In cases with severe kyphosis, osteotomies are essential to reconstruct the sagittal alignment. Various techniques have been described for correcting post-tubercular kyphosis, including pedicle subtraction osteotomy [ 8 ], closing-opening wedge osteotomy [ 9 , 10 ], and vertebral column resection [ 11 18 ]. Due to the complexity of severe post-tubercular kyphosis and accompanying late-onset neurological deficits, posterior vertebral column resection (PVCR) seems to be the most effective surgery that allows for sufficient correction of the deformity and decompression of the spinal cord [ 12 14 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wafa and Elbadrawi in their 40 cases study of PVCR, found that the mean operative time is 249minute and blood loss 850ml. 2,8 In this case, operation time was 330minutes with blood loss 1800ml. More time consumed and blood loss as a consequence of bony union in the anterior column.…”
Section: Discussionmentioning
confidence: 88%
“…3 Данные пациента З., 11 лет, с патологическим переломом Th 7 позвонка (по данным исследования операционного материала -хронический неспецифический спондилит) Th 7 , угловой грудной кифоз Th 6 -Th 8 38°: а -МРТ перед операцией; б -операционные фотографии на этапах коррекции дистрактором Caspar: введение винтов в тела позвонков, установка титановой блок-решетки; в -рентгенологический контроль дистракции; г -рентгенограммы позвоночника после операции: остаточный кифоз 9°, коррекция деформации 29°а Формирование угловых кифозов, достигающих 60° и более, встречается на фоне естественного течения туберкулезного спондилита в 3-5 % случаев [13]. Ретроспективный анализ 17 случаев VCR при данной патологии свидетельствует как о коррекции деформации в среднем на 68,7 ± 6,5 %, так и о высоких средних показателях кровопотери (M = 2218 мл) и длительности операции (6 ч 4 мин) [14]. Модифицированный вариант задней вертебротомии через дугу позвонка у детей с посттуберкулезными угловыми кифозами в возрасте 11 ± 5 лет позволил снизить продолжительность операции в среднем до 4 ч 16 мин и кровопотерю до 870 мл [15], что, остается весьма значительным показателем и при пересчете на ОЦК достигает 40 %.…”
Section: Discussionunclassified